Efficacy of low-dose rituximab versus immunosuppressants in refractory orbital inflammatory pseudotumors with intracranial extension - Li, Yuyu; Sun, Mingming; Xu, Xintong; Chen, Biyue; Chen, Xiyun; Wang, Yuhang; Xu, Quangang; Zhou, Huanfen; Wei, Shihui (Frontiers in Immunology, 2025)
ObjectiveThe aim of this study was to compare the efficacy of low-dose rituximab (RTX) and immunosuppressants in treating orbital inflammatory pseudotumor (OIP) with intracranial extension, a refractory and high-relapse disease.MethodsPatients who had been diagnosed with refractory OIP with intracranial extension and who were refractory to systemic corticosteroids were retrospectively recruited at the Neuro-Ophthalmology Department at the Chinese People’s Liberation Army General Hospital between December 2018 and September 2022. After methylprednisolone pulse therapy, we added 2 mg of tacrolimus per day, 1500 mg of mycophenolate mofetil per day, or 200 mg of rituximab at days 1 and 15, and then monitored those with CD19+ B cells of under 1% as adjuvant therapy.ResultsEleven patients (six males and five females) were included, with a mean age of 45.5 ± 11.8 years (age range: 21–64 years). The average follow-up period was 3.8 years (range: 2–5). Eight patients (72.7%) had different levels of decreased vision at onset of the illness and four patients (36.4%) had severely impaired vision (three with no light perception, one with some light perception). Four patients (36.4%) showed clinical course worsening or lack of remission when treated with corticosteroids. Seven patients (63.6%) had a typical relapsing course, and the annual recurrence rate was higher than 7.36 ± 3.73 times. Of these seven, four (57.1%, 4/7) were able to undergo successful management with immunosuppressants. Three (42.9%, 3/7) failed with immunosuppressants but succeeded in controlling relapse with RTX.ConclusionOIP with intracranial extension is uncommon. More than half of patients with OIP with intracranial extension may be satisfactorily treated with corticosteroids combined with immunosuppressants. However, for patients who still experience recurrence or slow reduction of lesions after applying this combined therapy, RTX may be a better option.